PENENTUAN RUTE di APLIKASI GOOGLE MAPS DENGAN MENGGUNAKAN GRAF DAN ALGORITMA PRIM - Winda Ade Fitriya B; Sitti Rosnafi’an Sumardi; Nicea Roona Paranoan; Caecilia Bintang Girik Allo (Universitas Pahlawan Tuanku Tambusai, 2023)
Along with the times, many technologies and applications were created to meet human needs. Applications that are quite developed at this time is a navigation application. One of the well-known and frequently used navigation applications is Google Maps. By using the Google Maps application, people can find out where they are and know the route to get to their destination very easily. This paper discusses route selection in the Google Maps application using the prim graph and algorithm. Keywords: Graph, Prims’s Algorithm Prim, Route, Application